Comparisons and evaluation of aerosol burden and optical depth in CMIP5 simulations over East Asia. (15th September 2020) - Li, Ruolin; Ma, Xiaoyan; Xiong, Feilin; Jia, Hailing; Sha, Tong; Tian, Rong
Abstract: Aerosol plays an important role in the climate system by affecting the radiative and energy balances. Hence, in this paper, the spatial patterns of aerosol burden and aerosol optical properties (AOD) in four the Coupled Model Intercomparison Project phase 5 (CMIP5) models over East Asia during 2001–2005 are compared to quantify inter-model differences and to evaluate AOD simulations against observations. The evaluation of AOD against Moderate Resolution Imaging Spectroradiometer (MODIS) satellite retrievals shows that CMIP5 models can reproduce the spatial pattern of MODIS AOD reasonably well. The mean AOD over eastern China shows that NorESM1-M underestimates MODIS AOD by 40%, due to the lack of emissions of some aerosol components, such as nitrate, biogenic aerosol, and non-desert mineral dust. In contrast to that, CSIRO-Mk3.6.0 overestimates annual mean of MODIS AOD over eastern China by 20%, partially caused by larger aerosol emissions and burden. Compared to MODIS AOD, GFDL-CM3 performs the best in simulating AOD in eastern China, because ammonium and nitrate are included in this model. The comparisons of CMIP5 and Aerosol Robotic Network (AERONET) AOD show similar results. In addition, the simulated AOD values are closer to AERONET AOD in Mongolia, China, Japan and Korea than that in India. The results also reveal that there are some inter-model differences of aerosol burden over East Asia, caused by the inter-model differences of aerosol emissions, wet scavenging, and transport. Over eastern and northwestern China and the west Pacific, the inter-model differences of anthropogenic aerosol burden and spatial variabilities are smaller than that of natural aerosol burden. Highlights: The evaluation results show that CMIP5 models can reproduce the spatial pattern of MODIS AOD reasonably well. Compared to MODIS AOD, GFDL-CM3 performs the best in simulating AOD in eastern China. The simulated AOD values are closer to AERONET AOD in Mongolia, China, Japan and Korea than that in India. The inter-model differences of aerosol burden are caused by aerosol emissions, wet scavenging, and transport.